Analysis of the Relationship Between Characteristics and Participation in Community Forest Management Activities in Sipoholon District North Tapanuli Regency - Samosir, Nursani; Hamzah, Hamzah; Mt Napitupulu, Dompak (Rifa'Institute, 2025)
Introduction: The Community Forestry (HKm) program aims to empower forest farmer groups through sustainable management. Active participation from farmer groups is essential to ensure that land use does not damage the ecosystem, as well as paying attention to the socio-economic aspects of group members, such as income levels, education, and access to technology. Purpose: Analyzing the relationship between participation and the socio-economic characteristics of KTH members in HKM management activities in Sipoholon District, North Tapanuli Regency. Method: The approach used in this research is descriptive quantitative. This research will be conducted in 3 KTHs located in Sipoholon District, Tapanuli Regency, namely KTH Dolok Imun Lestari located in Simarpinggan, Huta Raja Hasundutan Village, Sipoholon District. KTH Dos Roha and KTH Lumban Gaol Lestari located in Simanungkalit Village, Simanungkalit Village, Sipoholon District, North Tapanuli Regency, North Sumatra. Result and Discussion: Only a few aspects of socio-economic characteristics have a strong relationship with involvement in HKm management activities, while most others do not have a significant effect. This finding is important to be the basis for planning empowerment programs, with a focus on factors that truly encourage active community participation. Conclusion: Based on socio-economic characteristics, income, number of dependents, cosmopolitanism and leadership are correlated with participation, while socio-economic characteristics such as age, education, land area and incentives are not correlated with participation.